Intrahousehold rights and decision-making regarding water in two counties in Kenya - Nchanji, Eileen Bogweh; Guettou Djurfeldt, Nadia; Zaremba, Haley Carter (2023)
The primary aim of this study is to explore what the local water sources are, how they are prioritized, how communities are coping with water scarcity, how water is locally governed and controlled, and how decision-making dynamics at the household as well as community levels impact the choice and use of improved and unimproved water sources, as well as the differentiated impacts these choices have on women and men. Rural households in Kenya must make a complex set of decisions around water source choices as they lack secure water access, particularly during the dry season. The study communities of Bomani and Kidzini North rely on multiple sources of water to choose from that are of different quality and reliability, with a large share of households relying on unimproved water sources, such as unprotected dams and water pans. Even these unimproved water sources become scarce in the dry season and in periods of prolonged drought. As such, this study seeks to understand what coping mechanisms are being used by community members when water and money run out. Qualitative analysis is used to examine what benefits and trade-offs are associated with these strategies, and how these benefits and trade-offs impact men and women differently due to socially prescribed gender roles.